Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14106120
|View full text |Cite
|
Sign up to set email alerts
|

Band-Sensitive Calibration of Low-Cost PM2.5 Sensors by LSTM Model with Dynamically Weighted Loss Function

Abstract: Particulate matter has become one of the major issues in environmental sustainability, and its accurate measurement has grown in importance recently. Low-cost sensors (LCS) have been widely used to measure particulate concentration, but concerns about their accuracy remain. Previous research has shown that LCS data can be successfully calibrated using various machine learning algorithms. In this study, for better calibration, dynamic weight was introduced to the loss function of the LSTM model to amplify the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The parameter y i is the label data in pixel i , i.e., the bias of the geophysical a priori PM 2.5 versus ground monitor PM 2.5 . N is the total number of training datasets input to the model in one training step.Few previous studies have customized the loss function for deep learning methods in PM 2.5 estimation. In this study, we identified shortcomings associated with employing the MSE loss function for training a global CNN PM 2.5 model. These deficiencies encompass disregard for regions characterized by low PM 2.5 concentrations and the production of unreasonable estimations in areas with limited monitor coverage.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…The parameter y i is the label data in pixel i , i.e., the bias of the geophysical a priori PM 2.5 versus ground monitor PM 2.5 . N is the total number of training datasets input to the model in one training step.Few previous studies have customized the loss function for deep learning methods in PM 2.5 estimation. In this study, we identified shortcomings associated with employing the MSE loss function for training a global CNN PM 2.5 model. These deficiencies encompass disregard for regions characterized by low PM 2.5 concentrations and the production of unreasonable estimations in areas with limited monitor coverage.…”
Section: Data Sources and Methodsmentioning
confidence: 99%